Topotactic Phase Transformation in Epitaxial SrCo1‐xFexO3−δ Thin Films. (28th February 2020) - Nguyen, Hien Thi Dieu; Granville, Simon; Seidel, Jan
Abstract: Epitaxial perovskite (P) and brownmillerite (BM) SrCo0.67 Fe0.33 O3− δ thin films grown on (100) SrTiO3 substrates by pulsed laser deposition are investigated by detailed X‐ray diffraction, conductive AFM, and SQUID magnetometry measurements regarding their structural, electronic, and magnetic properties. A topotactic phase transition between P and BM phases can be utilized to oxidize the material to stoichiometric perovskite SrCoO3.0 by wet‐chemical oxidation with NaClO. The material exhibits weak magnetic properties up to room temperature and an additional clear ferromagnetic transition near 50 K. Abstract : Epitaxial perovskite and brownmillerite SrCo0.67 Fe0.33 O3− δ thin films grown on (100) SrTiO3 substrates by pulsed laser deposition are investigated by detailed X‐ray diffraction, conductive AFM, and SQUID magnetometry. A topotactic phase transition between perovskite and Brownmillerite phases is identified. The material exhibits weak magnetic properties up to room temperature and an additional clear ferromagnetic transition near 50 K.